Plasmonic lattice excitation of surface acoustic waves in silicon photonic circuits - Leroy Dokhanian; Saawan Kumar Bag; Mirit Hen; Inbar Shafir; Matan Slook; Shai Ben-Ami; Avi Zadok (APL Photonics)
Surface acoustic waves enable long group delays and narrowband analog filtering on-chip, which are difficult to obtain with fast-moving electromagnetic waves. Surface acoustic waves have been introduced to silicon photonics through the absorption of modulated pump light in gratings of metallic elements and subsequent thermoelastic actuation. In this work, acoustic waves are excited through a plasmonic surface lattice of nano-antennas, which exhibits enhanced resonant absorption of incident light. The stronger absorption increases the intensity of the acoustic waves by a factor of 50. The devices are used in an electro-opto-mechanical, microwave-photonic oscillator and improve its linewidth and noise performance by 2–3 orders of magnitude. The results represent a major improvement in surface acoustic wave–photonic devices and a new application for plasmonics within silicon photonic circuits.